2014
DOI: 10.1371/currents.hd.2c56ceef7f9f8e239a59ecf2d94cddac
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Two-Year Intensive Multidisciplinary Rehabilitation Program for Patients with Huntington’s Disease: a Prospective Intervention Study

Abstract: Objective: To assess effects of a two year intensive, multidisciplinary rehabilitation program for patients with early- to mid-stage Huntington’s disease. Design: A prospective intervention study. Setting: One inpatient rehabilitation center in Norway. Subjects: 10 patients, with early- to mid-stage Huntington’s disease. Interventions: A two year rehabilitation program, consisting of six admissions of three weeks each, and two evaluation stays approximately three months after the third and sixth rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 24 publications
3
41
0
1
Order By: Relevance
“…Studies in HD animal models suggest that exercise improves motor function, 6 delays the progression of cognitive dysfunction, 6 and provides neuroprotection in the form of delayed disease onset. 7,8 In recent years, several small scale feasibility studies have investigated the effects of exercise and physical therapy in HD [9][10][11][12][13][14][15] with improvements observed in dynamic balance, 9,1010,11 gait speed, function and level of physical activity, 10,14 fitness, 13 cognitive function, 16 neuroplasticity, 16 and self-reported quality of life measures. 11,12 These studies included early to mid-stage participants, and although they demonstrated proof-of-concept, were underpowered to establish efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in HD animal models suggest that exercise improves motor function, 6 delays the progression of cognitive dysfunction, 6 and provides neuroprotection in the form of delayed disease onset. 7,8 In recent years, several small scale feasibility studies have investigated the effects of exercise and physical therapy in HD [9][10][11][12][13][14][15] with improvements observed in dynamic balance, 9,1010,11 gait speed, function and level of physical activity, 10,14 fitness, 13 cognitive function, 16 neuroplasticity, 16 and self-reported quality of life measures. 11,12 These studies included early to mid-stage participants, and although they demonstrated proof-of-concept, were underpowered to establish efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The initial search yielded 2,377 records that ultimately resulted in 18 quantitative articles and 2 qualitative included articles [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ; a flowchart is available in our published systematic review. 5 The updated search included 5 additional quantitative articles [31][32][33][34][35] and 1 additional qualitative article, 36 resulting in a total of 23 quantitative and 3 qualitative studies reviewed.…”
Section: Literature Searchmentioning
confidence: 99%
“…5 There are no proven neuroprotective agents for HD and although symptomatic therapies exist, impairments in physical function continue to develop and worsen as the disease progresses. [13][14][15][16][17][18] Such interventions have the capacity to therapeutically address motor and cognitive aspects of the disease, which has been robustly demonstrated in HD mouse models using environmental enrichment. The effects of multidisciplinary therapy interventions, encompassing both physical and cognitive therapy, have been less well studied in patients with HD.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of multidisciplinary therapy interventions, encompassing both physical and cognitive therapy, have been less well studied in patients with HD. [13][14][15][16][17][18] Such interventions have the capacity to therapeutically address motor and cognitive aspects of the disease, which has been robustly demonstrated in HD mouse models using environmental enrichment. [19][20][21] Preliminary, uncontrolled trials on inpatient multidisciplinary therapy have reported positive effects on physical function, mood and quality of life.…”
Section: Introductionmentioning
confidence: 99%